2021
DOI: 10.1002/bsl.2530
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile homicide offenders: Why they were involved in serious crime

Abstract: The perpetration of murders by juveniles (individuals under age 18) has been a serious concern in the United States since the 1960s. As a result of four decisions by the United States Supreme Court during the 21st century, the likelihood that juvenile homicide offenders will be released back into society is substantially higher than it was in the year 2000. Given these changes in sentencing policies and practices, understanding why youths under 18 engage in homicidal behavior is more important than ever for tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Parental relationships are the main source of support for young children (Yule et al, 2019). Therefore, providing children who do not have positive adult role models with positive influences may be beneficial to decrease negative behaviors (Heide, 2021). School personnel, including school nurses, can help fulfill this role.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…Parental relationships are the main source of support for young children (Yule et al, 2019). Therefore, providing children who do not have positive adult role models with positive influences may be beneficial to decrease negative behaviors (Heide, 2021). School personnel, including school nurses, can help fulfill this role.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…There is scant literature focused on why juveniles commit homicide. In a small study of teens involved in homicide, the two dominant themes included establishing an identity and coping with painful and angry emotions associated with family situations and trauma (Heide, 2021).…”
Section: The Role Of Emotions and Thoughts And Their Impact On Violencementioning
confidence: 99%
“…In six of these studies, JHOs were released from juvenile correctional facilities [8,10,[27][28][29][30]. In the other seven studies, JHOs were released from adult prisons [9,[31][32][33][34][35][36]. Eleven of the studies were conducted with U.S. samples, and the remaining two studies were conducted in the Netherlands [10] and Canada [36].…”
Section: General Samples Of Incarcerated Jhosmentioning
confidence: 99%
“…In a subsequent study that focused on the JHOs' motivations for engaging in serious criminal behavior before incarceration, Heide [34] found that the psychological (e.g., search for identity) and sociological (e.g., subcultural values) factors identified by the men as influential in their decision to offend were evenly split for the 18 JHOs in the sample. The reasons for criminal involvement did not significantly differentiate between the JHOs who were reincarcerated and those who were not reincarcerated.…”
Section: General Samples Of Incarcerated Jhosmentioning
confidence: 99%